(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Turbulent flow modelling has increasingly become one of the main scientific research occupations, seeking to develop a universal modelling approach that can describe accurately the dynamics of all turbulent flow scales. Modern attempts try to bring together two main objectives; the applicability of the turbulent flow models to complex flow configurations of industrial interest as well as reducing the computational costs needed for their resolution. Large Eddy Simulation (LES) modelling approach has many promising features among all other turbulent flow modelling approaches such as RANS or DNS. In this study, LES modelling approach has been demonstrated and applied to turbulent channel flow at moderate Reynolds number using Fluent solver. The obtained turbulent flow statistics were compared to their corresponding values of a detailed, well resolved DNS simulation. The obtained LES turbulent flow statistics have an acceptable trend to those of the reference DNS results, which reflects the validity of the LES approach to model turbulent flows accurately and encourages its use in predicting turbulent motion for industrial and engineering applications.